Antibacterial activity of Some mouthwash Solutions against Staphylococcus lentus Isolated from Mouth Infections - Alash, Sameer Abdulameer; Mohammed, Maoj Qassim (Iraqi Journal of Science, 2019)
A total of nine swab samples were collected from inflamed teeth and gingiva of humanâ€™soral cavity from a dentist clinic in Baghdad. All specimens were cultured in Mitis Salivarius agar medium and the isolated bacterial pure colonies werethen identified by using VITEK2. Three samples were diagnosed and identified as Staphylococcus lentus. One of the three isolates which showed a distinctive heavy growth on the media was selected for further analysis in this study. Paper disk diffusion method was used to detect the antibacterial activityof three of mouthwash solutions (Zak, Colgate and Listerine). The results showed that â€œColgateâ€ was the most active solution with antibacterial activity compared with the other two solutions.